Determinants of Islamic banking performance in OIC member countries - Bobbo Amadou; Hamed Salim Yazid (African Governance and Development Institute (AGDI), 2023)
The aim of this article is to identify the determinants of the performance of Islamic banks by examining the relative contribution of the said determinants in the member countries of the Organization of Islamic Cooperation (OIC). The methodology used is based on a multivariate framework, in particular, Generalized Least Squares and the Generalized Method of Moments. From a set of quarterly data of 20 OIC member countries collected over the period 2013 to 2020, we find that: i) liquidity ratio, profitability ratio and presence of compliance committee in sharia improve the performance of Islamic banks. ii) Liquidity ratio and presence of Shariah compliance committee are found to be more important in influencing the performance of Islamic banks in OIC member countries with respective weights of 0.510 and 0.699. It is therefore up to the actors of the Islamic banking sector of the OIC member countries to establish an overall governance policy framework and to comply with the rules and principles of the Islamic Shariah while maintaining strict control over the various transactions, which will lead to the reduction of costs and will make it possible to take measures which can contribute to increasing their resources and their investments which will make it possible to make economies of scale.
Keywords: 330; OIC; Islamic Bank; Performance; GMM